Development of Metacognitive Strategies to Improve Performance in High-Complexity Clinical Tasks Among Nursing Students: An Experimental Study - L. Iván Mayor-Silva; Alfonso Meneses-Monroy; Marta M. Hernández-Martín; Domingo de Pedro; José Luis Mate-Muñoz; Guillermo Moreno (Nurse Educator, 2026)
Purpose: This study evaluates the effect exerted by a metacognitive skills training program on nursing students’ metacognitive skills and their perception regarding mental workload in high-load clinical situations. Methods: An experimental design with control and experimental groups (1:1) was conducted with first- and fourth-year nursing students. The experimental group completed 2 high-load simulations with metacognitive training between them, while the control group only performed the simulations. Both groups repeated the experience after 8 days without intervention. Task overload was measured using the NASA Task Load Index and the Metacognitive Awareness Inventory. Results: A significantly higher Metacognitive Awareness Inventory score was observed in the experimental group 8 days after intervention in both academic years ( P = .002). Mental demand decreased among the fourth-year students from the experimental group immediately after the intervention ( P = .027) and at day 8 ( P = .038). Temporal demand decreased among fourth-year students after the intervention ( P < .001) and at day 8 ( P < .001). Physical demand was significantly lower in the fourth-year students from the experimental group after the intervention ( P = .005), while their performance scores were significantly higher after the intervention ( P = .005) and at day 8 ( P = .006). Conclusions: Metacognitive training reduced perceived demands among fourth-year nursing students, suggesting improved cognitive efficiency during simulation.